Enhanced chemical looping gasification of biomass coupled with CO2 splitting based on carbon negative emission. (15th May 2022) - Wei, Guoqiang; Deng, Lifang; Yuan, Haoran; Yang, Xixian; Huang, Zhen; Zheng, Anqing; Xu, Li
Graphical abstract: Highlights: CLGCS was proposed to produce syngas and split CO2 . Reaction equilibrium and intermetallic synergy mechanism were discussed. The improvement order of heterologous metal on OCs was Co2 O3 >NiO >CeO2 >CaO. CO2 conversion73.5% was remained after 20 cyclic reaction. Reaction path of NiO modified OC was confirmed. Abstract: Under the background of fossil fuel consumption and global climate change, an enhanced chemical looping gasification of biomass coupled with CO2 splitting (CLGCS) was proposed in this work to produce high-quality syngas from biomass and split CO2 into CO by using Fe-based mixed oxygen carriers (OCs) without extra catalyst and excessive energy consumption, which provided a carbon negative emission technology for the cascade conversion of biomass and resource utilization of greenhouse gas. The reaction equilibrium and regulation mechanism of CLGCS were analyzed in Ellingham diagrams via theoretical calculation. Variable conditions were designed and performed to investigate the reaction performance of OCs. The intermetallic synergy was analyzed, and the improvement order of heterologous metal on lattice oxygen transfer of OCs was Co2 O3 > NiO > CeO2 > CaO. The NiO modified sample exhibited excellent reaction behavior in CLGCS, which provided active sites for catalytic cracking of tar in CLG stage and activating CO2 molecules in splitting stage. Syngas with heating value 13.32 MJ/m 3 and carbon conversion 74.18% were achieved in CLG stage, corresponding to CO2 conversion 64.09% and CO yield 23.59 mmol/g in splitting stage. High temperature enhanced the endothermic reactions in CLGCS process, and the biomass occurrence ratio indicated a positive correlation with CO2 splitting. Although some OC particles agglomerated in reaction process, the pore structure and reactivity remained stable. After 20 cyclic reaction tests, the carbon conversion in CLG stage and CO2 conversion in splitting stage were kept at 67.52% and 73.5%, respectively. The reaction path of CLGCS with NiO modified OC was summarized as: Fe2 O3 /NiFe2 O4 → Fe/FeO/Ni → Fe3 O4 /Ni → Fe2 O3 /NiFe2 O4 .